The short Oxford history of English literature - Sanders, Andrew (Oxford Univ. Press, 1996)
This book provides a comprehensive and introdutory guide to the history of English literature from Anglo-Saxon period to the present. The content of the book covers all major periods of English literature chronologically from Old English literature to Past-war literature including medieval literature, the Renaissance, Shakespeare, the literature of the seventeenth and eighteenth centuries, Romanticism, the Victorian period, and Modernism. The book discusses, in detail, the important writers and their works, including Scottish, Irish, and Welsh writing in English.